Sociopragmatics Competence in The Characteristics of Banyumas Community Blakasuta - Nurdiyanto, Erwita; Resticka, Gita Anggria (Journal of Pragmatics Research, 2021)
Banyumas people have characteristics and personalities that can be observed through the use of language. This is seen in terms of lexical peculiarities, tone of speech, and grammar structure. Banyumas language is used as the identity of banyumas people who are blakasuta (cablaka, thokmelong, outspoken). With this identity, it can be described how the sociopragmatics competence of banyumas people. This sociopragmatics competency is related to the ability of banyumas people to use language in accordance with certain social contexts or certain social conditions. which are understood by speakers and identify models of communication competencies in banyumas people who are blakasuta. The purpose of this study was to uncover the characteristics of blakasuta used in banyumas community and identify the forms of speech resulting in daily communication. This research is qualitative descriptive research using a sociopragmatics approach. The method of data collection uses observation techniques by interviewing directly to the informant. The results of this study show that the characteristics of banyumas people who are blakasuta can show the sociopragmatics competence of banyumas people in speech. Banyumas community communication patterns can be identified from the form of speech acts, type of speech acts, and speech acts strategy in each communication process. This cannot be separated from the cultural characteristics of banyumas people. Pragmatics competence relates to the cultural principles underlying the way banyumas people communicate, namely the principle of respecting others and the principle of avoiding open conflict to maintain a harmonious relationship.Keywords: Sociopragmatics, Blakasuta, Banyumas